Spin-Off Islamic Banking Window In Indonesia - Dedy Mainata; Parno Parno; Angrum Pratiwi; Irfan Irfan (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2023)
This article provides a discussion of some of the issues associated with Spin Off and areas that have not been critically discussed in the literature. Regulations in Indonesia require all Islamic Banking Windows to separate from their parent banks if the value of their assets reaches 50 percent of the total assets of their conventional banks or at least 15 years after the issuance of the regulation. This study is to find out how the Islamic Banking Windows spin-off is carried out, the reasons, readiness, impact, as well as criticism, suggestions and solutions to the spin-off policy. This qualitative research uses secondary data such as books, journals, articles by describing the spin-off problems comprehensively. We found 2 spin-off methods: establishing a new Islamic Commercial Bank (BUS) or transferring Islamic Banking Windows (UUS) rights and obligations to an existing BUS. A spin-off is important to do so that there is no mixing between conventional and Islamic so that there will be the development of purer Islamic products and increase customer trust and so that management is more independent in accordance with their respective businesses and can develop and compete. We also found a positive impact from the spin-off, namely increasing revenue, and accelerating the development and market share of BUS in Indonesia. The negative impact of spin-offs reduces the level of efficiency, the restructuring has not been properly controlled, the availability of networks and infrastructure is not adequate, and the stress of employees due to different leadership styles, organizational culture, or company orientation. Lastly, we find that UUS is not ready to do a spin-off before 2023 with the main problem, the capital. We suggest that regulators postpone their mandatory spin-off policy by 2023 and suggest other options such as mergers or conversions.